2011
DOI: 10.1371/journal.pone.0016226
|View full text |Cite
|
Sign up to set email alerts
|

Stabilization by Fusion to the C-terminus of Hyperthermophile Sulfolobus tokodaii RNase HI: A Possibility of Protein Stabilization Tag

Abstract: RNase HI from the hyperthermophile Sulfolobus tokodaii (Sto-RNase HI) is stabilized by its C-terminal residues. In this work, the stabilization effect of the Sto-RNase HI C-terminal residues was investigated in detail by thermodynamic measurements of the stability of variants lacking the disulfide bond (C58/145A), or the six C-terminal residues (ΔC6) and by structural analysis of ΔC6. The results showed that the C-terminal does not affect overall structure and stabilization is caused by local interactions of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…The most similar structure was that of RNase HI from Sulfolobus tokodaii (Protein Data Bank (PDB) code: 3ALY, Z -score = 8.2, r.m.s.d. = 3.6 Å, sequence identity = 15%) ( 40 ). In addition, the structure of RNase HI from Bacillus halodurans in complex with an RNA/DNA hybrid (PDB code: 1ZBI, Z -score = 4.7, r.m.s.d.…”
Section: Resultsmentioning
confidence: 99%
“…The most similar structure was that of RNase HI from Sulfolobus tokodaii (Protein Data Bank (PDB) code: 3ALY, Z -score = 8.2, r.m.s.d. = 3.6 Å, sequence identity = 15%) ( 40 ). In addition, the structure of RNase HI from Bacillus halodurans in complex with an RNA/DNA hybrid (PDB code: 1ZBI, Z -score = 4.7, r.m.s.d.…”
Section: Resultsmentioning
confidence: 99%
“…Comparison of the crystal structure of LC11‐RNase H1 with that of Sto‐RNase H1ΔC620 indicates that the number of buried nonpolar residues and the number of ion pairs of LC11‐RNase H1 are comparable to those of Sto‐RNase H1ΔC6, while the number of buried charged residues and the total volume of cavities of LC11‐RNase H1 are higher than those of Sto‐RNase H1ΔC6 (Table I). These results suggest that LC11‐RNase H1 is destabilized as compared to Sto‐RNase H1 not only by removal of the C‐terminal anchoring tail but also by increasing the cavity volume and the number of buried charged residues.…”
Section: Resultsmentioning
confidence: 99%
“…A study by Takano et al demonstrated that the fusion of C-terminal residues of Sto-RNase HI to other proteins resulted in more stable chimeric proteins. [24] For in vivo application, it was demonstrated that biomaterials could be deliberately chosen for GF-based wound regeneration based on GF structural considerations, such as ionic properties, surface charges, and binding sites. [25] We chose the carbomer under the assumption that it plays a role not only in retaining the proteins at wound sites but also in providing an electrostatic binding moiety to positively charged bFGF due to its intrinsic anionic nature.…”
Section: Discussionmentioning
confidence: 99%